2022
DOI: 10.1093/nar/gkac050
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary rewiring of regulatory networks contributes to phenotypic differences between human and mouse orthologous genes

Abstract: Mouse models have been engineered to reveal the biological mechanisms of human diseases based on an assumption. The assumption is that orthologous genes underlie conserved phenotypes across species. However, genetically modified mouse orthologs of human genes do not often recapitulate human disease phenotypes which might be due to the molecular evolution of phenotypic differences across species from the time of the last common ancestor. Here, we systematically investigated the evolutionary divergence of regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…When performing comparisons between mouse and human lethal genes, several considerations need to be taken into account: 1) RNA expression profiles, including differences in developmental gene expression may reflect physiological differences between these two organisms 60,61 . This is supported by evidence of evolutionary divergence in regulatory networks contributing to phenotypic differences 62,63 ; 2) molecular function and biological processes are likely to remain constant between different species while physiological relevance may differ 64 ; 3) based on that, we may want to consider essential functions instead of essential genes, and approaches based on projection over functional modules, e.g. pathways or networks, have already been implemented 56 ; 4) even within the same species, we may observe variability due to genetic background, e.g.…”
Section: Discussionmentioning
confidence: 79%

Lethal phenotypes in Mendelian disorders

Cacheiro,
Lawson,
Van den Veyver
et al. 2024
Preprint
“…When performing comparisons between mouse and human lethal genes, several considerations need to be taken into account: 1) RNA expression profiles, including differences in developmental gene expression may reflect physiological differences between these two organisms 60,61 . This is supported by evidence of evolutionary divergence in regulatory networks contributing to phenotypic differences 62,63 ; 2) molecular function and biological processes are likely to remain constant between different species while physiological relevance may differ 64 ; 3) based on that, we may want to consider essential functions instead of essential genes, and approaches based on projection over functional modules, e.g. pathways or networks, have already been implemented 56 ; 4) even within the same species, we may observe variability due to genetic background, e.g.…”
Section: Discussionmentioning
confidence: 79%

Lethal phenotypes in Mendelian disorders

Cacheiro,
Lawson,
Van den Veyver
et al. 2024
Preprint
“…Although many genes and cellular processes are similar between humans and other mammals, the mapping of orthologous genes is imperfect, and gene and protein interaction patterns can vary between species due to the rewiring of regulatory and protein-protein interaction networks. 33 , 77 , 78 For this reason, work is ongoing to generate independent molecular interaction networks for mammalian species, including mice, 79 rats, 80 and cattle. 81 Network rewiring of interactions also occurs in different tissues and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that the roles of TFs in GRNs are almost identical between humans and mice ( Stergachis et al, 2014 ; Yue et al, 2014 ). Interestingly, Kim et al found that the rewiring of GRNs contributes to the phenotypic discrepancies that occur between humans and mice ( Ha et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%